Effect of Calcium Carbonate Residues from Cement Industries on the Phenolic Composition and Yield of Shiraz Grapes - Maya-Meraz, I.O.; Pérez-Leal, R.; Ornelas-Paz, J.J.; Jacobo-Cuéllar, J.L.; Rodríguez-Roque, M.J.; Yañez-Muñoz, R.M.; Cabello-Pasini, A. (South African Journal of Enology and Viticulture, 2020)
Phenolic compounds are secondary metabolites synthesised in response to biotic or abiotic stress in plants. This stress-induced increase in phenolic compound concentrations is generally activated by internal levels of abscisic acid (ABA). The exogenous application of ABA or calcium chloride on grapevines is also known to increase grape yield and alter the phenolic composition of grapes. Residues of cement industries such as calcium carbonates (CaCO3) are a safe environmental source of calcium that could be used to induce the synthesis of phenolic compounds and act as a yield promoter in grapes and other crops. Consequently, the objective of this study was to evaluate the effect of cement industries’ CaCO3 residues (CaCO3R) on the yield and concentration of phenolic compounds in Shiraz grapes. Thirteen phenolic compounds were identified and quantified by HPLC-DAD. Malvidin-3-O-glucoside was the major anthocyanin found in Shiraz grapes, and its concentration increased by more than 200% in CaCO3R-treated vines. Similarly, the concentration of cinnamic acid, the main precursor of phenolic compounds, increased by more than 900% in grapes treated with CaCO3 residues at harvest time. Finally, catechin, epicatechin and procyanidin B1 and B2 increased significantly at harvest time in CaCO3R-treated grapes relative to the controls. In general, it was found that foliar application of CaCO3 residues from the cement industry at véraison induced an increase in yield, and in the concentration and composition of phenolic compounds in grapes.